Home Appliances in the Smart Grid: A Heuristic Algorithm-Based Dynamic Scheduling Model - Abuznaid, Anan R.S.; Tutkun, Nedim (Frontier Energy System and Power Engineering, 2021)
Customers and power utilities alike will benefit from smart grid technology by lowering energy prices and regulating generating capability. The accuracy of information sharing between main grids and smart meters is critical to the performance of scheduling algorithms. Customers, on the other hand, are expected to plan loads, respond to electricity demand alerts, engage in energy bidding, and constantly track the utility company's energy rates. Consumer loyalty can be improved by strengthening the connectivity infrastructure between the service provider and its customers. We suggest a heuristic demand-side control model for automating the scheduling of smart home appliances in order to optimize the comfort of the customers involved. Simulation findings show that the suggested hybrid solution will reduce the peak-to-average ratio of overall energy demand while still lowering total energy costs without sacrificing consumer convenience